Basal Cell Carcinoma With Perineural Invasion: A Systematic Review and Pooled Survival Analysis. Issue 11 (7th November 2022) - Abushukur, Yasmine; Ibrahim, Yousef; Cascardo, Camilla; Keeley, Jacob; Knackstedt, Thomas
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Perineural invasion (PNI) is considered a high-risk histopathologic feature in many skin cancers. Perineural invasion is a well-known poor prognostic factor of squamous cell carcinoma, but is poorly understood in the context of basal cell carcinoma (BCC). OBJECTIVE: To analyze available demographic, clinical, and treatment data for BCC with PNI and the effect of these variables on recurrence patterns, disease progression, and cancer-specific mortality (CSM). METHODS: A systematic review and pooled-survival analysis was performed using case reports and series of patients with perineural BCC. RESULTS: This review included 159 patients from 49 publications. Of these cases, 57 patients reported at least one recurrence. Where reported, median follow-up time was 31 months for patients without recurrence ( n = 79) and 21 months for patients with recurrence ( n = 32). The cumulative incidence of CSM at 5 years was 8.5% (95% confidence interval [CI] 0.028–0.186) and the overall five-year survival was 90.9% (95% CI 0.796–0.961). CONCLUSION: Male gender, multifocal nerve involvement, presence of clinical symptoms, and PNI detected on imaging are associated with poor prognosis of BCC with PNI. The high rate of disease recurrence and suboptimal cumulative incidence of CSM highlights the importance of early clinical detection, before the onset of symptomatic PNI and multifocal nerve involvement.